P186 Inflammatory Bowel Disease Care in the Covid-19 pandemic era: Experience from a Tunisian gastroenterology department. (27th May 2021) - Dahmani, W; Sahar, N; Aya, H; Nour, E; Wafa, B A; Aida, B S; Ahlem, B; Mehdi, K; Hanene, J; Ali, J
Abstract: Background: The coronavarius disease (COVID-19) pandemic has brought forth a multitude of challenges for both patients having inflammatory bowel disease (IBD) and clinicians involved in their care. The national-wide lockdown in Tunisia, from Mars to Mai 2020 had substantially decreased healthcare accessibility and drugs availability. In addition, the uncertainty caused by the COVID-19 pandemic was likely to lead to anxiety and negative emotional and behavioral reactions which are thought to be predictors of active IBD and relapses. We aimed to assess the hospital admission and complication rates in patients with IBD during the first wave of COIVD-19 infection in Tunisia and to compare them to those observed during the same period one year earlier. Methods: We retrospectively analyzed the clinical features of patients with IBD admitted to our department during the period of time following the national lock-down in Tunisia ( from Mai, the 4th to August, the 31th). We compared the total global admission rate, IBD related complications, surgery rates and postoperative complications between the study period (P1) and the corresponding period of the previous year (P2 : from Mai, the 4th to August, the 31th, 2019). The Chi square test and Fisher exact test were used for analysis of categorical data. Results: Eighty patients with IBD were included in this study (44 patients in P1 and 36 patients in P2), 73.7% of which (n=59) had Crohn disease. The sex ratio was 1.16 and the mean age was33.8 years ± 11.9. The mean follow-up period was 5 years. In 17.5% of cases (n=14), the IBD was diagnosed during the admission. None of the P1 patients had tested positive for SARS-CoV-2. The incidence of hospitalizations during P1 was 2.6 per week. It was greater than that of P2 but without the difference being statistically significant (2.1 admissions per week; incidence rate ratio: 0.34; 95% CI: 0.67-1.2; p = 0, 54). A total of 31 complications were noted (19 in P1 vs 12 in P2; p=0, 489). The complications were as follows: 19 cases of acute severe colitis (12 in P1 vs 7 in P2 ; p= 0, 234), 8 cases of intra-abdominal abscesses (6 in P1 vs 2 in P2 ; p=0, 234), 4 cases of acute intestinal obstruction (1 in P1 vs 3 in P2 ; p=0, 322). Among patients who had presented an acute severe colitis, 6 had undergone subtotal colectomy (6 in P1 vs 0 in P2, p=0, 006). Conclusion: Our study showed that during the pandemic period, there was an increase in the incidence of hospitalizations of patients with IBD as well as a significant increase in the need for surgery in severe acute colitis. These results should be taken into account so that IBD management strategies can be adjusted accordingly, if the COVID-19 pandemic persists or recurs, or in case of future outbreaks.